2018
DOI: 10.1371/journal.pone.0190817
|View full text |Cite
|
Sign up to set email alerts
|

Probing the changes in gene expression due to α-crystallin mutations in mouse models of hereditary human cataract

Abstract: The mammalian eye lens expresses a high concentration of crystallins (α, β and γ-crystallins) to maintain the refractive index essential for lens transparency. Crystallins are long-lived proteins that do not turnover throughout life. The structural destabilization of crystallins by UV exposure, glycation, oxidative stress and mutations in crystallin genes leads to protein aggregation and development of cataracts. Several destabilizing mutations in crystallin genes are linked with human autosomal dominant hered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Over 90% of lens proteins are in the crystallin family (3), which maintain clear vision by retaining a high amount of native β-sheet secondary structures. Crystallins remain soluble for decades at high concentrations, since they are not regenerated in the organelle-free lens cells (4,5). While they are stable proteins, over time, UV light and other factors slowly damage crystallins (6), causing aggregation and, ultimately, cataract disease.…”
mentioning
confidence: 99%
“…Over 90% of lens proteins are in the crystallin family (3), which maintain clear vision by retaining a high amount of native β-sheet secondary structures. Crystallins remain soluble for decades at high concentrations, since they are not regenerated in the organelle-free lens cells (4,5). While they are stable proteins, over time, UV light and other factors slowly damage crystallins (6), causing aggregation and, ultimately, cataract disease.…”
mentioning
confidence: 99%
“…An increase in histones in lenses from the αA-R49C mutant mice may be indicative of an increase in nucleosome density, and a functional increase in the histone/DNA ratio may lead to increased amounts of heterochromatin. The increase in histone transcripts in Cryaa -R49C mice suggests that the increase in gene expression of histones may be an early event in cataractogenesis, though the notion that α-crystallin functions as a modulator of the expression of histones has not yet been investigated [16] . Nevertheless, these findings strongly suggest a functional relationship between histones and α-crystallin.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of oxidative stress, Hsp27 plays a role as an antioxidant, decreasing the ROS by raising levels of intracellular GSH [28,29]. It has been reported that mutation in HspB1 and/or αB-crystallin are responsible for the development of cataract [30] and are considered as major targets for the development of anti-cataract drugs [31]. We have previously reported that expression of Prdx6, an anti-oxidant protein, is decreased resulting in an increase in ROS in the LECs of SCRs [9].…”
Section: Discussionmentioning
confidence: 99%